Operations research: how it can strengthen food-aid programmes - Ruel, Marie T. (International Food Policy Research Institute, 2005)
Given the large amount of funds allocated to food-assisted Maternal and Child Health and Nutrition (MCHN) programmes. . .it is critical to improve their effectiveness. Operations research holds promise for helping achieve this goal. Effective programmes, in turn, can help accelerate progress toward improved child nutrition, health, and survival.”